Estudo do comportamento da lipase comercial Lipozyme RM IM em reações de esterificação para obtenção de biodiesel - Erika C. G. Aguieiras; Susana L. Souza; Marta A. P. Langone (Química Nova, 2013)
The aim of this work was to study monoalkyl ester synthesis catalyzed by immobilized lipase Lipozyme RM IM via the esterification reaction. Yields of over 90% were obtained with butanol in esterification reactions with oleic acid. In the reactions with deodorizer distillates of vegetable oils and butanol, the conversion obtained was greater than 80% after 2.5 h. For the esterification reaction of palm fatty acid deodorizer distillate (PFAD) and butanol, seven reuse cycles of Lipozyme RM IM were carried out and the final conversion was 42% lower than the initial conversion.